Evaluation of the Nurse-Saul method using maturity sensors for concrete strength control - Utepov, Ye.B.; Aniskin, A.; Tulebekova, A.S.; Akhazhanov, S.B.; Zharassov, Sh.Zh. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The article presents the results of experimental studies on the strength of concrete grade B25 brand M350 by direct and indirect methods of control. To conduct tests, 17 cylindrical, 15 small, and 2 large cubic specimens were manufactured. 15 cylindrical specimens by 3 pieces were tested for compression in a hydraulic press on 1, 3, 7, 14, and 28 days of curing, and in the remaining two for 28 days the curing temperature was measured in order to obtain the strength-maturity relationship by the method of Nurse-Saul. The curing temperatures of the larger specimens were measured similarly, from which the concrete maturity and strength values on days 1, 3, 7, 14, and 28 were estimated. On the same days, compression tests were carried out on small specimens and by the shock pulse method on large specimens. As a result, the strength gain curves were obtained and calibration dependencies were plotted. The calibration dependencies showed a sufficiently close convergence of the results of the direct method of control (i.e., compression of small specimens) and the Nurse-Saul method of maturity, in contrast to those of the shock pulse method. The determination coefficients of these dependencies amounted to 0.9357 and 0.8965, respectively.
Бетонның беріктігін бақылау үшін кемелдену датчиктерін қолдану арқылы Nurse-Saul әдісін бағалау
Оценка метода Nurse-Saul с применением датчиков зрелости для контроля прочности бетона
Keywords: maturity method; concrete strength; embedded sensors; compression test; curing temperature; shock-pulse method; calibration dependence